Experimental study and physical modeling of ceiling temperature distribution of fires in a large open-plan compartment with unilateral asymmetric openings - Xiaoyu Shan; Yuanzhou Li; Yong Jiang; Yong Hu (Case Studies in Thermal Engineering)
With the rapid emergence of large open-plan architectural structures, there is a need to reevaluate the applicability of fire standards based on smaller compartment fire dynamics. More investigation is required to gain a deeper understanding of the associated fire characteristics. Therefore, this paper investigated experimentally and numerically the fire behavior and ceiling temperature distribution in a 1/4th-scaled large open-plan compartment with unilateral asymmetric openings, under several different-sized openings and fire sources. The results showed that an increase in the dimensions of the asymmetric openings positively impacted the combustion rate of the fire source and the flame inclination; the latter increased in the direction away from the opening. The previous classical models based on open confined spaces underestimated the maximum ceiling temperature, whereas the model relying on the virtual origins performed well. A critical opening size was found to minimize the buoyancy-driven plume component. Thus, a physical model suitable for predicting the longitudinal ceiling temperature distribution in large open-plan buildings was proposed, considering both the sizes of the fire source and openings. The new model demonstrated good agreement with experiments and improved understanding of fire dynamics in a large open-plan compartment with unilateral asymmetric openings.